Identification of the Melissopalynological Flora of Northern Punjab using Honey Bee Samples - Alam, Waqar; Khan, Qaisar Abbas; Ali, Hafiz Wajid; Kamal, Danish; Bibi, Iqra; Rizwan, Muhammad (Indus Journal of Bioscience Research, 2025)
Melissopalynology, the study of pollen contained in honey, plays a pivotal role in elucidating the dynamics of pollination and the underlying biodiversity essential for ecological health. This research utilizes melissopalynological techniques to meticulously examine honey bee samples from Northern Punjab, focusing on the diverse biotopes encompassing agricultural lands, urban environments, and forest areas. Employing advanced microscopy and robust statistical methodologies, the study investigates the variations in pollen composition across different seasons, thereby shedding light on the complex interactions between bees and their floral environment. The findings from this study reveal distinct seasonal patterns of pollen availability, which are critical for optimizing agricultural practices and enhancing crop productivity. During spring, there is a notable increase in pollen diversity, corresponding with a peak in floral blooms. In contrast, winter samples show reduced diversity, reflecting the scarcity of blooming plants during the colder months. Spatial analysis further demonstrates that the type of biotope significantly influences the pollen profiles; agricultural areas predominantly yield pollen from crop plants, forests are rich in native floral species, and urban areas present a mixture of ornamental and invasive plant species. These insights are invaluable for informing sustainable agricultural practices and biodiversity conservation efforts. By understanding the seasonal and spatial variations in pollen sources, farmers can better align their planting and cultivation strategies to support bee health and ensure effective pollination. The study highlights the importance of maintaining diverse and native plant species in urban and forested areas to foster robust bee populations and ecological resilience. This research underscores the critical role of melissopalynology in enhancing our understanding of pollination processes, supporting agricultural sustainability, and promoting biodiversity conservation in Northern Punjab.